Evaluation of humoral and cellular immune responses in healthcare workers with varying levels of SARS-CoV-2 exposure: effects of CoronaVac vaccination followed by heterologous booster - Gomes, Shayane Martins Rodrigues; Ribeiro-Alves, Marcelo; Ribeiro, Roberto Stefan de Almeida; Brito, Andréia Carolinne de Souza; Lisboa, Vinicius da Cunha; Azevedo, Samara Galdino de; Nogueira, Jeane de Souza; Castilho, Leda dos Reis; Pôrto, Luís Cristóvão Sobrino; da Silva, Silvia Amaral Gonçalves; Dutra, Patrícia Maria Lourenço; Manfro, Wânia Ferraz Pereira; et al. (Frontiers in Immunology, 2025)
BackgroundThe COVID-19 pandemic demanded diverse vaccination strategies, and there is significant interest in their effectiveness in generating a robust immune response. In Brazil, the use of CoronaVac was crucial in reducing mortality; however, heterologous booster doses were necessary to enhance memory immune response. This study aimed to evaluate the humoral and cellular immunity in healthcare workers who were vaccinated with a complete regimen of CoronaVac and subsequently received heterologous booster doses over nearly one year.MethodsA longitudinal study recruited healthcare professionals with varying levels of exposure to SARS-CoV-2 from the Health Complex of the Rio de Janeiro State University (UERJ), Rio de Janeiro, Brazil. Blood samples were collected at five time points, including baseline and after vaccination with CoronaVac and heterologous booster doses (ChAdOx1 nCov-19 or BNT162b2). The Th1/Th2/Th17 cytokine production was measured by Flow Cytometry, using whole blood samples stimulated or not with the SARS-CoV-2 Spike protein. In parallel, serum levels of IgG antibodies against Spike (anti-S) and Nucleocapsid (anti-N) proteins were assessed using an immunoassay. Adjustments were made for confounding factors, including age, sex, level of SARS-CoV-2 exposure, and COVID-19 infection status.ResultsOur results demonstrate that CoronaVac induced high anti-S IgG levels at all evaluated time points (P<0.01). Cytokine analysis revealed a sustained production of antigen-specific Th1 cytokines, including IL-2 (P<0.01) and IFN-γ (P<0.05) regardless of level of SARS-CoV-2 exposure or previous COVID-19 infection at any point during the study. Additionally, we identified six moderate to strong positive correlations (P<0.0001): IL-10 and IFN-γ (ρ=0.77), IL-6 and TNF (ρ=0.77), IL-2 and IFN-γ (ρ=0.71), IL-6 and IL-10 (ρ=0.66), anti-N IgG and anti-S IgG (ρ=0.62), and IL-2 and anti-S IgG (ρ=0.62).ConclusionThe CoronaVac elicited an antigen-specific cellular immune response, characterized by enhancing the production of key cytokines such as IFN-γ and IL-2, with high levels of anti-S IgG. Furthermore, the administration of heterologous boosters significantly enhanced these immune responses, demonstrating induced-specific immunological response. These findings underscore the importance of primary vaccination and boosters in inducing immune protection against COVID-19, potentially informing future vaccination policies and approaches.